2010
DOI: 10.1097/ypg.0b013e32833a2220
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T is not a risk factor for autism spectrum disorders in South Brazil

Abstract: Many studies have suggested that autism may be associated with metabolic abnormalities in the folate/homocysteine pathway, which is involved in DNA methylation, thus altering gene expression. One of the most important polymorphisms in this pathway is C677T of the methylenetetrahydrofolate reductase gene, because the T allele is associated with a decrease in enzymatic activity. We evaluated the association between C677T polymorphism and autism spectrum disorders through a case--control study. In addition, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 19 publications
2
30
2
Order By: Relevance
“…There are conflicting reports suggesting both a positive and negative association of MTHFR C677T polymorphism with autism [45,46]. In our study, a positive association was observed between MTHFR C677T variant allele and autism risk.…”
Section: Discussioncontrasting
confidence: 41%
“…There are conflicting reports suggesting both a positive and negative association of MTHFR C677T polymorphism with autism [45,46]. In our study, a positive association was observed between MTHFR C677T variant allele and autism risk.…”
Section: Discussioncontrasting
confidence: 41%
“…A similar study with the Chinese Han population also supported the notion that MTHFR C677T polymorphism is associated with increased risk of ASD [34]. However, a study performed in south Brazil showed that MTHFR C677T alone is not a risk factor for ASD [35].…”
Section: Discussionsupporting
confidence: 52%
“…The MTHFR C677T polymorphism converts an alanine residue to a valine (ALA222VAL), leading to a lower enzymatic activity Mansoor et al, 2009). Some studies have shown that autism might be associated with metabolic abnormalities in the folate/homocysteine pathway, which is involved in DNA methylation, thus altering gene expression (dos Santos et al, 2010). The association between the MTHFR C677T polymorphisms and risk of autism is still controversial and ambiguous ( James et al, 2006;Rogers, 2008;Goin-Kochel et al, 2009;Mohammad et al, 2009;Pasca et al, 2009;dos Santos et al, 2010;Liu et al, 2011;Schmidt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%